Effectiveness of Ear Acupuncture Therapy and Behavioral Therapy in Children with ADHD - Dwijayanti, Niken Arum; Haryanto, Joko Tri; Badri, Sholichan; Wardoyo, Suwaji Handaru (Jurnal Ners, 2023)
ADHD (Attention Deficit Hyperactivity Disorder) is one of the neurodevelopmental disorder. ADHD characterized by signs and symptoms such as inattention, hyperactivity, and impulsive. The purpose of this research was to determine the effectiveness of ear acupuncture therapy and behavioral therapy in children with ADHD. This research used Quasy Experimental Design with pretest and posttest design. This research was conducted in February-April 2023 at SLB Autis Alamanda and SLB Harmony Surakarta. The sample is children with ADHD who met the inclusion and exclusion criteria. The sample was divided into two groups, 15 children each group. Ear acupuncture therapy using earseeds at point zero, shenmen point, and liver point. Behavioral therapy using ABA method (Applied Behavioral Analysis). Data were analyzed using Independent Sample T-test. The result of this test showed that significance value is 0.849 (p > 0.05). The conclusion of this research is ear acupuncture therapy and behavioral therapy were not effective to decrease ADHD behavior in children at SLB Autis Alamanda and SLB Harmony Surakarta.